Travel mode and tour complexity: The roles of fuel price and built environment - Michael Simora; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Despite steady increases in fuel economy, CO2 emissions from road transportation in Germany are on the rise, increasing by nearly 4% since 2009. This study analyzes the impact of different policy levers for bucking this trend, focusing specifically on the role of fuel prices and features of the built environment. We estimate two multinomial logit models, one addressing work-related tours and the other non-work related tours. Both models consider two interrelated dimensions of travel on the extensive margin: mode choice and tour complexity. We use the model estimates to predict outcome probabilities for different levels of our policy variables. Our results suggest significant effects of the built environment – measured by bike path density, urbanization, and proximity to public transit – in discouraging car use and increasing tour complexity. Fuel prices, by contrast, appear to have little bearing on these choices. – – Trotz stetiger Verbesserungen der Kraftstoffeffizienz sind die CO2-Emissionen im Verkehrssektor in Deutschland seit 2009 um ca. 4 Prozent gestiegen. Die vorliegende Studie analysiert die Auswirkungen verschiedener politischer Handlungsoptionen, um diesem Trend entgegen zu wirken, mit besonderem Fokus auf der Rolle des Kraftstoffpreises sowie infrastrukturellen Begebenheiten. Wir schätzen zwei multinomial logit Modelle, zum einen bezüglich arbeitsbezogener Touren und zum anderen bezüglich nicht-arbeitsbezogener Touren. Beide Modelle betrachten jeweils zwei zueinander in Wechselbeziehung stehende Merkmale der individuellen Mobilitätsentscheidung: den Transportmodus und die Tourkomplexität. Darüber hinaus verwenden wir die Schätzergebnisse, um Wahrscheinlichkeiten der einzelnen Entscheidungen bei variierenden infrastrukturellen Begebenheiten vorherzusagen. Unsere Ergebnisse legen nahe, dass eine höhere Dichte an Fahrradwegen, eine stärkere Urbanisierung, sowie mehr Nähe zum öffentlichen Nahverkehr die Autonutzung signifikant reduzieren und die Tourkomplexität signifikant erhöhen. Hingegen scheinen Kraftstoffpreise nur einen geringen Effekt auf diese Entscheidungen zu haben.
Keywords: D10; R48; R42; 330; activity-based approach; travel mode choice; tour complexity; multinomial logit; predicted probabilities